«La elva leve»: Alta-saken som rollespill i historieundervisninga - Bergum Johanson, Lisbeth; Pedersen, Helge Christian (UiT Norges arktiske universitet, 2019)
The annual staging of a role play for school pupils called “La elva leve” (‘Let the River Live’) at Alta museum addresses the conflict over the building of a hydroelectric power plant in the Alta-Kautokeino watercourse between 1978-82. The confrontation has an important legacy, not least by bringing the issue of Sámi Indigenous rights into the national limelight. This article discusses how the role play might serve as a starting point for teaching pupils about the conflict’s consequences for Sámi rights, and interrogates the degree to which this kind of role play might benefit the pupils’ awareness of history. Drawing on observations and interviews, we found that the pupils were strongly engaged in the play and that they found it both interesting and educational. However, while they also gained more knowledge about the conflict itself, there was little evidence that they connected the conflict to the Sámi struggle for indigenous rights, or that their historical consciousness expanded significantly.